Analisis Dinamika Kesetaraan Gender dalam Pengajaran Bahasa Inggris - Zaitun Qamariah (Badan Penerbit STIEPARI Press, 2024)
This paper outlines gender dynamics in English language teaching (ELT) which includes challenges, strategies, curriculum design, and complex teacher-student relationships. It provides an overview of challenges such as gender bias, stereotyping, and unequal participation, as well as effective strategies to foster an inclusive learning environment. In addition, this study also outlines perspectives on gender inclusiveness, highlights the importance of cultural sensitivity and intersectionality and offers valuable insights for teachers and policy makers to promote gender equality in teaching practices in the ELT domain.